Improvement of interfacial shear strengths of polybenzobisoxazole fiber/epoxy resin composite by n‐TiO2 coating. Issue 4 (17th May 2012) - Qian, Jun; Wu, Junling; Liu, Xiaoyun; Zhuang, Qixin; Han, Zhewen
Abstract: Smooth polybenzobisoxazole (PBO) fiber has limited interfacial interaction with resin matrix. In this article, nano‐TiO2 coating on PBO fiber is applied to improve the interfacial adhesion between PBO fiber and epoxy resin. The test results suggest that the PBO fiber had good interaction with epoxy resin matrix after its treatment with n‐TiO2 sol. Nano TiO2 particle embedded onto PBO fiber surface, acting as a chock, which made fiber implanted into the resin better. This greatly improved the shear strengths (IFSS) of PBO fiber/epoxy resin composite. It has been found that a 56% increase in interfacial IFSS has achieved without sacrificing mechanical properties of fiber. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013 Abstract :